RESEARCH OF LEVEL OF PARTICULAR COMPONENT OF CREATIVE THINKING - KŘÍŽOVSKÁ, Ilona (Trends in education, 2008)
The article presents results of research of level of particular component of creative thinking. It describes briefly methodics of test and analyses results of the research. Moreover it shows problematic concerning curence of used methodics.
Keywords: creativity; diagnostic; fluence; flexibility; originality; elaboration